PENGEMBANGAN MEDIA PRISMA PUTAR PADA MATERI MAKHLUK HIDUP KELAS III SEKOLAH DASAR - Sakti, Rio Agusti Prabowo; Saidah, Karimatus; Wenda, Dhian Dwi Nur (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Learning that only relies on books and pictures often makes students bored during the learning process. Education in modern times requires teachers to continue to innovate in learning, product development needs to be done to improve the quality of learning. The need for media that is attractive and can be touched directly so that students are more motivated in the learning process. The purpose of this study was to determine the feasibility of rotating prism media. The product developed is expected to increase learning motivation in grade III elementary school students. This development research uses the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). This product is considered quite easy to use and is not linked to only one material because it is easy to replace with other materials.